PENURUNAN KADAR COD AIR LIMBAH INDUSTRI PERMEN DENGAN MENGGUNAKAN REAKTOR LUMPUR AKTIF - Titiresmi Adyananto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Pollution in the rivers is generally caused by domestic and industrial waste.Some treatments to solve it can be done individually or collectively. Theeffort can be physical, chemical, or biological treatments chosen by itsform, character, kind, quality, quantity. PT Van Melle Indonesia is a candycompany which produces a high biological waste with COD concentration10000-30000 mg/litre. This paper reports activated sludge reactorperformance to decrease the waste’s organic content. The reactor is abiological waste water treatment, as a sequence of earlier anaerob processwhich still has a high COD (700-4000 mg/litre). A continued reactoroperation done with retention time variation 24 hours, 18 hours, 12 hours,and 6 hours show reduced COD varied 80-90%. The highest efficiencywas 97.59% from the 24 hours retention time, and the lowest efficiencywas 89.5% from the 6 hours retention time.